Mexico : Report on Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2003)
This data module of the Report on Observance of Standards and Codes (ROSC) for Mexico contains a brief assessment of dissemination practices relative to the Special Data Dissemination Standards (SDDS) of the IMF. The findings reveal that dissemination of data subject to the SDDS is in observance of all SDDS specifications, including data coverage, periodicity, timeliness, and the dissemination of advance data release calendars. In several cases, the periodicity and timeliness of these data exceed SDDS requirements.